Mesenchymal stem cell-derived exosome subpopulations remained consistent for 28 culture days, displaying therapeutic effects in a silicosis mouse model - Lina Zhang; Jing Jin; Jing Jin; Liguang Sun; Gang Hou; Mingming Deng; Yiding Bian; Jianming Liu; Wei Cheng; Shaoliang Xing; Shaoliang Xing; Wenjia Wang; et al. (Frontiers in Cell and Developmental Biology)
IntroductionThe clinical translation of mesenchymal stem cell-derived exosome faces critical challenges in scalable production, subpopulation stability, and therapeutic route optimization. This study systematically addresses these barriers to advance exosome-based therapies.MethodsWe established a 28-day biomanufacturing workflow using a Hollow Fiber 3D bioreactor integrated with the RoosterBio exosome-harvesting system. Exosomes were subsequently purified and rigorously characterized at multiple production stages, followed by isotopically labeled with 89Zr for biodistribution studies. Therapeutic efficacy was evaluated in a silica-induced mouse silicosis model comparing intravenous and respiratory administration routes.ResultsOur findings indicate that (1) the RoosterBio exosome harvesting system in the Hollow Fiber 3D bioreactor enables 28 days production of exosomes, with stable harvesting of the main subpopulations over a certain period; (2) systemic administration via intravenous injection in rats reveals distinct tissue tropism, with isotope-labeled exosomes exhibiting predominant hepatic accumulation; and (3) in the silica-induced mouse silicosis model, respiratory delivery of exosomes significantly improves disease progression, whereas intravenous infusion of exosomes does not yield notable therapeutic effects.DiscussionThis study proposes a holistic workflow for early-stage development of natural exosomes as therapeutics, offering guidance on industrial-scale production, purification, and characterization of exosomes with stable subpopulation distribution and functional consistency. It further addresses administration route selection in pulmonary disease animal models and heterogeneity assessment of natural exosomes. These advancements facilitate clinical translation of exosome-based therapies.